The Translation Of Mythical And Folkloric Entities In Naguib Mahfouz’s Novel Layali Alf Layla Into English - Saqer Alderbashi, Bilal Mohammad (2021)
Mythology and folklore are essential parts of any culture. They evoke a tremendous amount of informative and expressive meanings and encapsulate various cultural backgrounds using a few lexical items. The mythical and folkloric lexical items (M&FLIs) found in literary discourse present an excellent opportunity to investigate the cultural concepts of these lexical items within a vivid literary context. Thus, the process of translating myths and folklore is better considered as an endeavour to aesthetically recreate the culture and literature of the source language (SL) and render them into the target language (TL) using appropriate translation strategies (TSs). The current study is an attempt to investigate the translatability of myths and folklore from Arabic into English. More specifically, it aims to examine the mythical and folkloric entities (M&FEs) in Naguib Mahfouz’s novel Layali Alf Layla and to explore the strategies used to translate them into English. This study relies on the methodology for systematic descriptive translation studies (DTS) and Baker’s taxonomy (2018) on the one hand and James’s (1980) two-step procedure of contrastive analysis (CA) on the other. The Arabic lexical items are located, listed, and described within their cultural and linguistic context to carry out the study. Their counterparts in the English translation are also located and discussed, taking into consideration their cultural and linguistic background.